Using Songs in Developing Intercultural Competence - Shayakhmetova, Liliia; Shayakhmetova, Leysan; Ashrapova, Alsu; Zhuravleva, Yevgeniya (Journal of History Culture and Art Research, 2017)
Songs in teaching English are not used to the full extent. To confirm this, we created a set of exercises based on the use of songs to form socio-cultural and regional knowledge, to familiarize students with the culture and way of life of Great Britain, to gain a deeper understanding of the representatives of this linguistic cultural community. The next step was carrying out a survey on revealing the effectiveness of using songs in EFL class, more precisely their effect on the developing of intercultural competence. Following methods were used to conduct the survey: the questionnaire of teachers and students, to determine the role of English songs in the developing of intercultural competence; the analysis of English language course books to determine the presence of songs focusing on their cultural significance; Life in the UK Test, a test to check the knowledge of the history and culture of Britain. The results of the research showed the expediency of using song to develop intercultural competence. Moreover, use of songs aroused interest among students; they expressed the opinion that lyrics have a much deeper meaning and varied information than they thought before using them in English classes. They expressed a desire to continue using songs during classes in keeping with this approach.